Transcriptomic Analysis of Long-Term Protective Immunity Induced by Vaccination With Mycoplasma gallisepticum Strain ts-304 - Kulappu Arachchige, Sathya N.; Young, Neil D.; Kanci Condello, Anna; Omotainse, Oluwadamilola S.; Noormohammadi, Amir H.; Wawegama, Nadeeka K.; Browning, Glenn F. (Frontiers in Immunology, 2021)
Live attenuated vaccines are commonly used to control Mycoplasma gallisepticum infections in chickens. M. gallisepticum ts-304 is a novel live attenuated vaccine strain that has been shown to be safe and effective. In this study, the transcriptional profiles of genes in the tracheal mucosa in chickens challenged with the M. gallisepticum wild-type strain Ap3AS at 57 weeks after vaccination with ts-304 were explored and compared with the profiles of unvaccinated chickens that had been challenged with strain Ap3AS, unvaccinated and unchallenged chickens, and vaccinated but unchallenged chickens. At two weeks after challenge, pair-wise comparisons of transcription in vaccinated-only, vaccinated-and-challenged and unvaccinated and unchallenged birds detected no differences. However, the challenged-only birds had significant up-regulation in the transcription of genes and enrichment of gene ontologies, pathways and protein classes involved in infiltration and proliferation of inflammatory cells and immune responses mediated through enhanced cytokine and chemokine production and signalling, while those predicted to be involved in formation and motor movement of cilia and formation of the cellular cytoskeleton were significantly down-regulated. The transcriptional changes associated with the inflammatory response were less severe in these mature birds than in the relatively young birds examined in a previous study. The findings of this study demonstrated that vaccination with the attenuated M. gallisepticum strain ts-304 protects against the transcriptional changes associated with the inflammatory response and pathological changes in the tracheal mucosa caused by infection with M. gallisepticum in chickens for at least 57 weeks after vaccination.